2004
DOI: 10.1084/jem.20031975
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Thymic Stromal Lymphopoietin in CD4+ T Cell Development

Abstract: Thymic stromal lymphopoietin (TSLP) signals via a receptor comprising the interleukin (IL)-7 receptor α chain and a distinctive subunit, TSLP receptor (TSLPR), which is most related to the common cytokine receptor γ chain, γc. We have generated TSLPR knockout (KO) mice and found that although these mice had normal lymphocyte numbers, γc/TSLPR double KO mice had a greater lymphoid defect than γc KO mice. This indicates that TSLP contributes to lymphoid development and accounts for some of the residual lymphoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
224
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 36 publications
(48 reference statements)
17
224
1
1
Order By: Relevance
“…In Rag1 À/À hosts, there is a lack of T-cell competition for other factors important for CD8 1 T-cell survival, such as DCs expressing self-peptide-MHC (spMHC) and IL-15, which could also influence the fitness of F5 T cells. Additionally, IL-7Ra is also a component of the heterodimeric thymic stromal lymphopoietin (TSLP) receptor, that has also been implicated in maintenance of naïve CD4 1 T cells [27,28], and loss of signalling through this receptor could also be contributing to death of IL-7R -F5 T cells. Therefore we directly addressed the role of IL-7 in enhancing Tcell fitness by transferring the same cells to IL-7-deficient Rag1 À/À mice.…”
Section: Resultsmentioning
confidence: 99%
“…In Rag1 À/À hosts, there is a lack of T-cell competition for other factors important for CD8 1 T-cell survival, such as DCs expressing self-peptide-MHC (spMHC) and IL-15, which could also influence the fitness of F5 T cells. Additionally, IL-7Ra is also a component of the heterodimeric thymic stromal lymphopoietin (TSLP) receptor, that has also been implicated in maintenance of naïve CD4 1 T cells [27,28], and loss of signalling through this receptor could also be contributing to death of IL-7R -F5 T cells. Therefore we directly addressed the role of IL-7 in enhancing Tcell fitness by transferring the same cells to IL-7-deficient Rag1 À/À mice.…”
Section: Resultsmentioning
confidence: 99%
“…Much discussion has focused on species-specific actions of TSLP (11,15,24). TSLP was reported to have certain B cell and T cell-related actions in mice (10,11,25), whereas human TSLP was reported to activate DCs with only an indirect effect on CD4 ϩ T cells (15). Subsequently, studies in mice revealed that mouse TSLP could also act on DCs (11,12).…”
Section: Tslp Elevates Sensitivity Of Cd4 ϩ T Cells To Low Dose Of Il-2mentioning
confidence: 99%
“…In addition to its actions on B cells, like IL-7, mouse TSLP has roles in T cell biology (10). Specifically, TSLPR/␥ c double knockout (KO) mice have more impaired T cell development than ␥ c KO mice, T cell recovery is defective in sublethally irradiated TSLPR KO mice, TSLP increases the proliferation and survival of CD4 ϩ single positive thymocytes and peripheral T cells, and finally, peripheral TSLPR KO CD4 ϩ T cells exhibit defective expansion in ␥ c /Rag2 KO-irradiated hosts (10).…”
mentioning
confidence: 99%
“…Alternatively, the absence of a large portion of the lymphocyte pool could also alter the stoichiometry of APCs available to present Ag to the responding CD8 T cells, thus enhancing memory generation in the IL-7 Ϫ/Ϫ mice. Finally, IL-7R␣ can form heterodimers with the thymic stromal lymphopoietin receptor (TSLPR) that specifically binds TSLP (27,28), a cytokine important for CD4 development and homeostasis (29,30). Signaling through the TSLPR, however, does not appear to influence IL-7R␣ expression as in vivo blocking studies using an anti-TSLP-R mAb failed to impact IL-7R␣ expression kinetics on Ag-specific CD8 T cells in both wild-type and IL-7 Ϫ/Ϫ mice following infection (data not shown).…”
Section: Il-7-deficient Environment Does Not Alter Il-7r␣ Expression mentioning
confidence: 99%